Understanding atmospheric methane sub-seasonal variability over India. (15th February 2020) - Tiwari, Yogesh K.; Guha, Tania; Valsala, Vinu; Lopez, Alfonso Saiz; Cuevas, Carlos; Fernandez, Rafael P.; Mahajan, Anoop S.
Abstract: Atmospheric methane (CH4 ) is considered to be one of the most important greenhouse gases due to its increasing atmospheric concentrations and the fact that it has a warming potential 28 times that of atmospheric carbon dioxide (CO2 ). Over the Indian sub-continent, fluxes and transport both contribute towards CH4 seasonal variability. Its intra-seasonal variability however is more complex as it is additionally influenced by monsoonal activity during the Asian Summer Monsoon (ASM) period. In this study, the intra-seasonal variability of atmospheric CH4 is examined using ground-based observations at two sites located in the Southern Indian Peninsula, Sinhagad (SNG) and Cape Rama (CRI); and outputs from three different model simulations. Both, the ground based observations and multi-model simulations show that the dominant spectral variability of CH4 is coherent with 20–90 day oscillations in the dynamics of the monsoon (termed hereafter as Intra-Seasonal Oscillations, ISOs). The multi-model analysis revealed that CH4 is heavily influenced by advection due to this intra-seasonal variability. The simulations also display a clear northward propagation of CH4 anomalies over India. The co-evolution of CH4, outgoing long wave radiation (to represent convection) and OH radicals (proxy to CH4 sinks) is presented. The study quantifies CH4 variability at intra-seasonal timescales and also its spatial extent. The results suggest that the effect of ISOs on CH4 needs to be considered along with the corresponding observations for future inverse modeling. Graphical abstract: Image 1 Composite analysis shows a clear northward propagation of atmospheric CH4 concentration anomalies with amplitude of ±10 ppb and at a speed of approximately 1.5° latitude per day. On the day when the active spell commences (i.e. at zero on the time axis), the CH4 concentrations switches from positive to negative at surface, middle and upper troposphere. This is visible in three different model outputs analyzed here although with some differences from model to model.Figure: Active-break composite evolution of atmospheric CH4 anomalies (ppb) over India, as simulated by models LMDz (upper left panel), ACTM (upper right panel), and CAM-Chem (lower panel). The data was averaged from 55 °E to 110 °E and is shown from the equator to 30 °N. Highlights: Surface CH4 observations in India show coherence of 30–90 day oscillations. Advected CH4 signal shows clear northward propagation of anomalies during JJAS. The co-evolutions of CH4, OLR, and OH radicals are presented for the JJAS period.